(untitled) (Research, Society and Development, 2024)
Knowledge about the impact generated by biological activity in soils is fundamental, as the organisms present play an essential role in various processes that occur in the soil environment. This study aims to evaluate the effect of different management practices on the invertebrate macrofauna present in litter in mountain environments in the State of Rio de Janeiro. Two agricultural areas were selected, one cultivated with tomatoes (Solanum lycopersicum L.) and the other with corn (Zea mays L.), in addition to a forest fragment area. Sampling of invertebrate macrofauna from the litter was carried out using a 25 x 25 cm template, with five samples being collected per area. The organisms were identified and quantified to estimate the density of individuals per square meter and to calculate frequency, richness, and ecological indices. Furthermore, the data were subjected to principal component analysis (PCA). In areas with tomato and corn cultivation, low frequencies of invertebrate macrofauna were observed. The low density of groups in the cultivation areas resulted in lower values of richness and diversity. The values observed in the cultivation areas are directly related to the management practices adopted in both areas. In the forest area, values of frequency, density, richness, and ecological indices were consistent with the stability of a natural system. The soil management system, with conventional cultivation and the use of pesticides, negatively influenced the community of litter macrofauna organisms.